An Impact Study of Harborview Plaza, La Crosse, Wisconsin - Klaus, William D. (My University, 1974)
The study investigates the impact of Harborview Plaza, which is the urban renewal project of the La Crosse river front area. This paper includes a short history of the events that led to the deterioration of the area. Some of the questions examined are: what effect will the project have on the established businesses in the C.B.D., do businessmen view it as beneficial or as a threat to their existence, is it beneficial for the public, and what is the public reaction to Harborview. Much of the information for this study was obtained by personal interviews with the city engineer, city planner, and the La Crosse Redevelopment Authority. A search of the available literature was made. This was basically the La Crosse Tribune, reports by the city planner, and other studies made by different departments of the city that affect the water front area. To get the viewpoint of the city businesses, a questionnaire was distributed among downtown businessmen. A citizen survey was used to find out how Harborview was seen by the public and what the public expects from it. The results of the study are as follows: 1) La Crosse has already realized an increased tax base by the relocation of businesses to other areas of the city, 2) it is a general consensus that most businessmen are in favor of Harborview Plaza even if it poses certain problems, and 3) the public is in favor of the plaza.
Keywords: Harborview Plaza (La Crosse, Wis.); Urban renewal -- Wisconsin -- La Crosse